Talking to adults : the contribution of multiparty discourse to language acquisition - Blum-Kulka, Shoshana; Snow, Catherine E. (Lawrence Erlbaum Associates, 2002)
This volume provides a comprehensive and in-depth analysis of the contribution of multiparty intergenerational talk in a variety of cultures to the development of children's communicative capacities.